Peran Media Sosial Dalam Meningkatkan Partisipasi Pemilih Pemula Di Kalangan Mahasiswa Universitas Muhammadiyah Riau - Fitrah Maharani; Salsabilla Ronardi; Ilham Hudi; Meesy Anugrah Putri; Queen Shakira Azzahra; Alvi Nabilah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Novice voters are the type of voters who need to pay attention to their level of political participation. The importance of the role of social media is needed because of the lack of awareness and low political education for beginner voters so that it can reduce their participation rate in general elections. The aim is to find out the importance of the role of social media in increasing the participation of novice voters among students of Muhammadiyah Riau University. This research uses a descriptive qualitative method by collecting data and research facts about the role of social media and beginner voters among students. The existence of social media requires the government and political parties to immediately respond to all comments. Nowadays, people can communicate directly with these institutions to voice their opinions, provide comments, and even submit their demands. First-time voters can participate in politics through various digital platforms. This phenomenon creates a new era in political participation, known as digital political participation or more simply referred to as online political participation. Social media is now the cheapest, fastest and most effective communication tool. It is inevitable how important the role of social media is in politics to attract people's attention through campaigns, teach the younger generation about politics, and increase the participation of first-time voters.